Good Governance Pada Pelayanan Publik di Kecamatan Borobudur - Setyawati, Sri Martamaningtyas; Rumsari Hadi Sumarto (Journal of Indonesian Rural and Regional Government, 2025)
Public services are required to implement the principles of good governance in order to achieve transparency, accountability, and public participation. However, limited human resources in information technology remain an obstacle, including in Borobudur District. This study aims to determine good governance in public services in Borobudur District and the challenges faced. This study uses a qualitative descriptive method. Data were obtained through interviews, observations, and documentation, then analyzed by describing the experiences of the research subjects and the actual conditions faced by service users. The results show that Borobudur District has implemented the three main principles of good governance. Transparency is realized through online services (Instagram, website, and WhatsApp) and the provision of information through bulletin boards and socialization, as well as the provision of physical symbols and visual identities of the subdistrict. Accountability is reflected in the implementation of E-SAKIP, performance reports, and public accountability forums, while community participation is evident from the involvement of citizens in surveys and evaluations of public services. However, the main challenge faced is the limited capacity of the apparatus to utilize information technology. Thus, this study answers the research focus that the implementation of good governance in Borobudur Subdistrict is already underway, but strengthening the competence of human resources in the use of digital technology and increasing synergy with the community needs to be continued so that public services become more transparent, accountable, participatory, and oriented towards community satisfaction.